Aquatic weeds diversity of Fatki River in Magura district, Bangladesh - Adhikary, Ripon Kumar; Alam, Md Shahin; Abdulla-Al-Asif, - (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The study was conducted at Fatki River under Magura district to learn the aquatic weeds diversity and abundance. This paper focused on species variation, number of species, water quality parameter and identification of aquatic weeds. It was assessed by collecting samples from Chukinogor Ghat, Kechuadubi and Arpara bazar during May to August, 2016. Aquatic weeds were abundant in rainy season and the semi-aquatic weeds were available almost all the year round. According to this study, total 22 species belonging to 12 orders, 16 families and 21 genuses were found. Again, 46%, 28%, 26% of total aquatic weeds percentages identified from the Chukinogor Ghat, Kechuadubi and Arpara bazar respectively. During this study period, nine species of family Pontederiaceae, Convolvulaceae, Menyanthaceae, Asteraceae, Poaceae, Araceae, Amaranthaceae, Polygonaceae were common in Chukinogor Ghat, Kechuadubi and Arpara bazar. Noticeable species– Lemna minor, Marsilea quadrifolia, Ludwigia palustris, Aeschynomene aspera, Najas graminea, Hydrilla verticillata, Najas guadalupensis, Utricularia inflate were only found in Chukinogor Ghat. This species are easily adapted in large areas. On the other hands, two species were common in Chukinogor Ghat, Kechuadubi – Pistia stratiotes and Equisetum hyemale. Prominent species of Arpara bazar were Cyperus rotundus and Xanthium indicum. Total 11 species of aquatic weeds were mainly recognized from these Kechuadubi, while greatest number was recorded of 20 species from Chukinogor Ghat and 12 species were have its place to Arpara bazar. Management technique and water quality parameters were also studied during study period and the temperature was recorded 29.0-30.00 ºC in Chukinogor Ghat, same as 28.0-320 ºC in Kechuadubi. Furthermore, 29.0-31.00 ºC temperature was found in Arpara bazar. DO levels were stable at ranged from7.0-7.5 ppm in Chukinogor Ghat and 4.7-5.3 ppm was recorded in two experimental Kechuadubi 4.5-5.0 in Arpara bazar respectively. This difference may arise due to the using of aerator in the Chukinogor Ghat same as decomposition, intensity of light in Kechuadubi and Arpara bazar. Transparency was 28-32cm in Chukinogor Ghat, 36-44cm in Kechuadubi, and 38-42 cm in Arpara bazar. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 201-207